A rapid, sensitive and accurate determination of cobalamin with double monitoring system: HPLC-UV and HPLC-ICP-OES - Bodur, Suleyman; Erarpat, Sezin; Balcik, Utku; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2021)
This study proposed a novel analytical method for the separation and determination of cobalamin and cobalt in kefir samples by high performance liquid chromatography-inductively coupled plasma-optical emission spectrometry (HPLC-ICP-OES) in addition to determination of cobalamin in HPLC system. Chromatographic parameters such as column type, buffer solution, mobile phase flow rate and sample injection volume were individually studied and optimized. In addition, cobalamin was simultaneously determined by high performance liquid chromatography with ultraviolet detection (HPLC-UV). LOD values of cobalt in cobalamin and cobalt for HPLC-ICP-OES system were calculated as 0.07 mg/kg (as Co) and 0.06 mg/kg, respectively. Recovery studies were conducted to evaluate the accuracy/applicability of the method. Recovery results for cobalt in cobalamin and cobalt detected by the HPLC-ICP-OES system were calculated in the range of 87.4-100.1 and 98.8-115.0%, respectively while recovery results for cobalamin were found to be between 89.2 and 98.3% for HPLC-UV system.
Keywords: Cobalamin; Cobalt; High-performance liquid chromatography; Inductively coupled plasma-optic emission spectrometry; Kefir; PERFORMANCE LIQUID-CHROMATOGRAPHY; DAIRY-PRODUCTS; VITAMIN-B-12; EXTRACTION; MICROEXTRACTION; SAMPLES; NICKEL; MILK; Chemistry; Food Science & Technology; Nutrition & Dietetics